Dependence of the Green’s function of a linear extension of a dynamical system on a torus upon a parameter - Bodnaruk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the dependence of the Green’s function of a linear extension of a dynamical system on a torus upon a parameter.